Assessing the Safety and Efficacy of Self-Expanding Metallic Y Stents in a Community Medicine Setting - Daniel Jacob Smith; Russell Vo; Parker Lachowsky; Ann Davis; Isha Puri; Sai Karan Vamsi Guda (Journal of Respiration)
Self-Expanding Metallic (SEM) Y stents are a newer form of stent that is gaining popularity outside the USA, but still has limited data, especially in a community medicine setting. This study analyzed efficacy and complication rates in 14 patients who had a SEM Y stent placed between August 2022 and June 2024 at Harris Methodist Hospital in Fort Worth, Texas for either central airway obstruction (CAO) or fistulae. Of the 14 patients, 11 were requiring supplemental oxygen or mechanical ventilation prior to stent placement. Post-stenting 42.9% had decreased oxygen requirements, 21.4% unchanged, 14.3% increased, and 21.4% remained on room air. Complications included mucus plugging (42.9%), infection (35.7%), and granulation tissue (14.3%). There was no statistically significant correlation between gender/age and complications (p = 0.879/0.490, respectively). Complication rates were similar when compared to silicone Y stents based on literature review. In conclusion, SEM Y stents are a safe and effective alternative stent intended for palliative treatment with similar success and complications that can be easily and effectively implemented in a community hospital, with the added benefit of being able to be placed with flexible bronchoscopy.